PENERAPAN MEDIA POSTER TERHADAP HASIL BELAJAR SEJARAH KEMERDEKAAN PADA SISWA TUNAGRAHITA Â - Onfiati, Sri (Pendidikan Luar Biasa, 2012)
Abstract; This study aims to examine the influence of media on the subject History of Independence poster against cognitive skills (understanding of the material) of children in special impaired and mentally retarded schools C YPPLB Ngawi. The study design used was